Non-invasive assessment of hepatic fibrosis among patients with chronic hepatitis B virus infection in three tertiary hospitals in Nigeria - Oguntoye Oluwatosin Oluwagbenga; Abdulkareem Lukman Olaitan; Umoru Benedict Ihiovi; Osasona Oluwadamilola Gideon; Ifeorah Ijeoma Maryjoy; Ariyo Olumuyiwa Elijah; Jegede Oluwatosin Samson; Oguntoye Oluwafunmilayo Adenike (SAGE Open Medicine, 2024)
Objective: This study aimed to assess hepatic fibrosis, using noninvasive tests, among patients with chronic hepatitis B virus infection in Nigeria. Methods: The study was a retrospective cross-sectional, hospital-based, multicentered study. The data of adult Nigerians who were aged 18 years and above who had been diagnosed with chronic hepatitis B infection and were not on treatment were extracted from three tertiary health institutions across Nigeria. Sociodemographic and relevant clinical data were obtained from the case notes of the patients. Fibrosis-4 and aspartate aminotransferase platelet ratio index scores were calculated to determine the presence and severity of liver fibrosis in the patients. The data obtained were analyzed using Statistical Package for the Social Sciences (version 25.0). A p -value of less than 0.05 was considered as statistically significant. Results: The data of a total of 234 patients were extracted for this study from across 3 tertiary hospitals in Nigeria. There were 132 (56.4%) males and 102 (43.6%) females in a ratio of 1.29:1 with a mean age of 37.92 ± 12.34 years. The fibrosis-4 score of the patients showed that 62.8% had “Normal/Mild Fibrosis,” 25.6% had “Moderate Fibrosis,” and 11.5% had “Severe Fibrosis/Cirrhosis.” The aspartate aminotransferase platelet ratio index score of the patients showed that 64.1% had “No Fibrosis,” 20.9% had “Mild Fibrosis,” 6.4% had “Moderate Fibrosis,” and 8.5% had “Severe Fibrosis/Cirrhosis.” The median fibrosis-4 score of the patients was 1.18 (0.77–1.74), while the median aspartate aminotransferase platelet ratio index score was 0.40 (0.26–0.69). Liver ultrasonography detected cirrhosis in 8.5% of the patients. All the patients were not yet on treatment for hepatitis B infection. Conclusion: The prevalence of hepatic fibrosis is high among patients with chronic hepatitis B virus infection in Nigeria and a large number of these patients were not yet on therapy. Noninvasive assessment of hepatic fibrosis should be considered as a critical part of the work-up of patients with chronic hepatitis B infection.